2019
DOI: 10.1111/pin.12827
|View full text |Cite
|
Sign up to set email alerts
|

Lower‐lobe predominant pleuroparenchymal fibroelastosis

Abstract: Upper‐lobe predominance of elastofibrosis is agreed upon for the diagnosis of clinical pleuroparenchymal fibroelastosis (PPFE). We herein describe a patient with dermatomyositis‐related interstitial pneumonia with a histology of lower‐lobe predominant PPFE. A 71‐year‐old woman who had been diagnosed with dermatomyositis‐related interstitial pneumonia died of respiratory failure. The computed tomography patterns of the lower lobes showed reticular and ground‐glass opacities with traction bronchiectasis. An auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…PH has been found in 19% of IPF patients with a mildly to moderately restricted respiratory function 20 and in 38-46% of those with advanced stage disease 21,22 . Although the prevalence of PH in IPPFE patients has not been investigated, there are a few case reports of PPFE patients with PH [23][24][25] . In this cohort, we found that four of 16 IPPFE patients (25%) were complicated with clinical PH.…”
Section: Discussionmentioning
confidence: 99%
“…PH has been found in 19% of IPF patients with a mildly to moderately restricted respiratory function 20 and in 38-46% of those with advanced stage disease 21,22 . Although the prevalence of PH in IPPFE patients has not been investigated, there are a few case reports of PPFE patients with PH [23][24][25] . In this cohort, we found that four of 16 IPPFE patients (25%) were complicated with clinical PH.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Differentiating PPFE from PAC may be challenging, given the similar histopathologic findings (Table 1). [6][7][8][9][10][11][12][13][14][15][16][17] A history of an underlying clinical condition associated with PPFE may influence the diagnosis. Likewise, PPFE is also suggested by the presence of atypical imaging features, exceeding the expected size of an apical cap (mean, 2.2 cm), 18 or secondary histologic findings of organizing airspace disease and small airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Although initially described as an upper lobe disease, the lower lobes can also be involved in PPFE, but less commonly [ 4 , 9 , 11 , 23 ]. When lower lobes are involved, an equal distribution between the upper and lower lobes can be observed in up to one third of the patients [ 24 ]. The radiologic pattern in the lower lobes can be similar to that in the upper lobes, with pleural thickening and fibrous bands extending toward the hilum; however, findings in the lower lobes may also show diffuse interstitial thickening, suggestive of a concomitant interstitial lung disease [ 4 , 7 , 8 , 11 , 13 , 16 ].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…A diagnosis of PPFE carries an overall poor prognosis, with 5-year survival rates of only 23.3–58.9% [ 7 , 8 , 14 , 24 ]. Two clinical scenarios have been described in the course of PPFE, that of a slow progression of disease and one with a more precipitous decline, with the former being the typical clinical course [ 4 , 30 ].…”
Section: Treatment Clinical Course and Prognosismentioning
confidence: 99%